How Do Latin American Migrants in the U.S. Stand on Schooling Premium? What Does It Reveal about Education Quality in Their Home Countries? - Daniel Alonso-Soto; Hugo \~Nopo (Institute of Labor Economics (IZA), 2017)
Indicators for quality of schooling are not only relatively new in the world but also unavailable for a sizable share of the world's population. In their absence, some proxy measures have been devised. One simple but powerful idea has been to use the schooling premium for migrant workers in the U.S. (Bratsberg and Terrell, 2002). In this paper we extend this idea and compute measures for the schooling premium of immigrant workers in the U.S. over a span of five decades. Focusing on those who graduated from either secondary or tertiary education in Latin American countries, we present comparative estimates of the evolution of such premia for both schooling levels. The results show that the schooling premia in Latin America have been steadily low throughout the whole period of analysis. The results stand after controlling for selective migration in different ways. This contradicts the popular belief in policy circles that the education quality of the region has deteriorated in recent years. In contrast, schooling premium in India shows an impressive improvement in recent decades, especially at the tertiary level.
Keywords: I26; J31; J61; 330; schooling premium; returns to education; wage differentials; immigrant workers